The Influence of Green Accounting on Greenhouse Gases in Public Companies - Suci Lailatul Sifa; Nurlaila Nurlaila; Hotbin Hasugian (Universitas KH. Abdul Chalim Mojokerto, 2025)
The purpose of this study is to examine the effect of green accounting (X) on greenhouse gas emissions (Y) in public companies. This study uses quantitative research. The sample used in this study was 300 companies listed in the Indonesian Sharia Stock Index (ISSI) for the 2021-2023 period. The data sources were secondary data from the Indonesian Stock Exchange, the Indonesian Sharia Stock Index, and related companies. Data analysis used was validity and reliability tests, simple linear regression, heteroscedasticity tests, multicollinearity tests, coefficient of determination, and hypothesis testing. Based on the results of the study on the effect of green accounting on greenhouse gas emissions in public companies, the following conclusions can be drawn: Simple linear regression analysis shows Y = 0.551 + 0.033 X, indicating a positive regression direction. This means there is a positive and increasing effect between green accounting (X) and greenhouse gas emissions (Y) in public companies. The results of the hypothesis test at a significance level of 0.05 can be seen that the calculated T (3.103) > T table (1.968) and p value 0.002 < 0.05, so the hypothesis is accepted explaining that green accounting (X) has a significant effect on greenhouse gases (Y) in public companies.